Fused placentas: Till birth do us part. (1st January 2021) - Lopez-Tello, Jorge; Sferruzzi-Perri, Amanda N.
Abstract: Twinning and placental fusion occur at a low frequency in species like humans and mice. They are linked to reduced birth weight and intertwin growth discrepancy with important consequences for perinatal survival. Despite this, little is known about the histological characteristics of the twin or fused placenta and how these relate to fetal growth. In this case report, we characterise the histological changes of a fused mouse placenta showing intertwin growth discrepancy. Our study demonstrates that morphological changes in the placental exchange and endocrine regions and elevated calcification levels may contribute to the intertwin growth discrepancy observed in mouse pregnancy. Highlights: Twinning and placental fusion occur at a low frequency in species, like mice. In this case report we show that placental fusion is linked with changes in the structure of the mouse placenta. Morphological changes are seen in both the exchange and endocrine regions of the placenta. There are also elevated levels of calcification in the placenta. Alterations in the fused placenta at least partly explain the intertwin growth discrepancy.